Laser beam scintillation with applications - Andrews, Larry C. (SPIE, 2001)
Renewed interest in laser communication systems has sparked development of useful new analytic models. This book discusses optical scintillation and its impact on system performance in free-space optical communication and laser radar applications, with a detailed look at propagation phenomena and the role of scintillation on system behavior. Intended for practicing engineers, scientists, and students.
"SPIE digital library."
Keywords: Optical communications.; Light -- Transmission.; elektronické knihy; electronic books